Teacher’s strategies in teaching mathematics and its relationship to mathematical and metacognitive skills for eighth graders in Amman governorate in Jordan - Nashaat Abdelaziz, Abdelqader Baioumy; Mohamad Zaidin, Mat@Mohamad; Basil Rasmi, Mansour Aljarrah (2020)
This study aimed to reveal the nature of the teaching strategies that eight-grade math teachers use and the relationship of these strategies with students' metacognitive and mathematical skills.The current study followed the descriptive analytical approach, as it studied the relationship of teachers’strategies in teaching mathematics with metacognitive and mathematical skills among eighth grade students in Amman Governorate, Jordan, and the researcher prepared and reconstructed several measures: the measure of teaching strategies, and the metric of metacognition skills and mathematical skills test. The tools were applied to a random sample of students and teachers, as the scale of teaching strategies was applied to a random sample of teachers of (150) mathematics teachers for the eighth grade, while the scale of metacognition skills and mathematical skills tests were applied to a random sample It reached (350) students in the eighth grade in Amman Governorate for the academic year 2019/2020. The results of the study showed that the eighth grade math teachers follow the various teaching strategies more than their dependence on the traditional methods of teaching, and the level of eighth grade students' metacognitive and mathematical skills was of a moderate degree, and the study concluded that there is a statistically significant correlation between the use of Mathematics teachers for the various teaching strategies and the level of metacognitive skills and mathematical skills for eighth graders.